13.1k views
3 votes
Find the sum of the first 12 terms of the sequence. If the answer is negative, do not enter any spaces in between the number and the negative sign. 1, -4, -9, -14, . . .

User Bullet
by
4.7k points

2 Answers

3 votes

Answer: -318

======================================

Step-by-step explanation:

The formula to use is

S = (n/2)*(2*a1+d*(n-1))

where

S = sum of the first n terms = unknown

n = number of terms = 12

d = common difference = -5

a1 = first term = 1

---------------------------------

So we get the following

S = (n/2)*(2*a1+d(n-1))

S = (12/2)*(2*1 + (-5)*(12-1))

S = 6*(2 - 5(11))

S = 6*(2 - 55)

S = 6*(-53)

S = -318

User Alona
by
4.9k points
4 votes

Answer:

-59

Step-by-step explanation:

1 - 5 = -4

-4 - 5 = -9

-9 - 5 = -14

-14 - 5 = -19

-19 - 5 = -24

-24 - 5 = -29

-29 - 5 = -34

-34 - 5 = -39

-39 - 5 = -44

-44 - 5 = -49

-49 - 5 = -54

-54 - 5 = -59

User Greenie
by
4.8k points